Ion beam profiling from the interaction with a freestanding 2D layer - Shorubalko, Ivan; Choi, Kyoungjun; Stiefel, Michael; Park, Hyung Gyu (Beilstein Journal of Nanotechnology, 2017)
Recent years have seen a great potential of the focused ion beam (FIB) technology for the nanometer-scale patterning of a freestanding two-dimensional (2D) layer. Experimentally determined sputtering yields of the perforation process can be quantitatively explained using the binary collision theory. The main peculiarity of the interaction between the ion beams and the suspended 2D material lies in the absence of collision cascades, featured by no interaction volume. Thus, the patterning resolution is directly set by the beam diameters. Here, we demonstrate pattern resolution beyond the beam size and precise profiling of the focused ion beams. We find out that FIB exposure time of individual pixels can influence the resultant pore diameter. In return, the pore dimension as a function of the exposure dose brings out the ion beam profiles. Using this method of determining an ion-beam point spread function, we verify a Gaussian profile of focused gallium ion beams. Graphene sputtering yield is extracted from the normalization of the measured Gaussian profiles, given a total beam current. Interestingly, profiling of unbeknown helium ion beams in this way results in asymmetry of the profile. Even triangular beam shapes are observed at certain helium FIB conditions, possibly attributable to the trimer nature of the beam source. Our method of profiling ion beams with 2D-layer perforation provides more information on ion beam profiles than the conventional sharp-edge scan method does.
Keywords: exposure dose; focused ion beam; freestanding 2D layer; graphene; ion beam diameter; ion beam point spread function